1985
DOI: 10.3758/bf03213364
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent observations of barpress suppression and freezing: Effects of CS modality and on-line vs. off-line training upon posttrial behavior

Abstract: In a conditioned suppression study with rats, CS modality (light vs. noise) and type of conditioning (on-line vs. off-line training) were manipulated. All rats were then tested on-line with only half the test trials reinforced. Some results and conclusions were as follows: (1) During initial training, suppression following reinforced noise trials was moderately strong at first but weakened over days; for the light, it was weak from the start. It was suggested that this strong influence of CS modality might com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
19
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
(21 reference statements)
5
19
0
Order By: Relevance
“…This observation of more freezing to tone than to light is consistent with other recent reports (Ayres et al, 1985;Sigmundi & Bolles, 1983), and it does not appear to be dependent upon some peculiarity of our tone and light CS. Modality differences in the ratio of freezing to "other" defensive behaviors could be partly responsible for the differences in judgments of conditioning to tone and light CSs, judgments based on the difference in lick suppression evoked by CS + versus CS -.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This observation of more freezing to tone than to light is consistent with other recent reports (Ayres et al, 1985;Sigmundi & Bolles, 1983), and it does not appear to be dependent upon some peculiarity of our tone and light CS. Modality differences in the ratio of freezing to "other" defensive behaviors could be partly responsible for the differences in judgments of conditioning to tone and light CSs, judgments based on the difference in lick suppression evoked by CS + versus CS -.…”
Section: Discussionsupporting
confidence: 81%
“…Unfortunately, from Sigmundi and Bolles (1983), Ayres et al (1985), and the present experiment, we do not gain a clear picture of what the "other" defensive behaviors are. We can only say that, in contrast to the suggestion of Ayres et al (1985), they do not seem to include rearing.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…When Ayres et al (1985) found similar barpress suppression to light and tone despite the greater freezing to tone, they too accepted that assumption. They assumed that if light evoked less freezing, then it must evoke more of some other defensive response that was equally incompatible with barpressing.…”
mentioning
confidence: 99%